Depression Among First- and Fifth-Year Medical Students in Riyadh, Saudi Arabia: - Almalki, Abdulaziz Saeed; Almalki, Abdullah; Kokandi, Abdullah; Aldosari, Bandar; Bin Baz, Abdulaziz; Alfadhel, Shoog; Alsuwayyigh, Abdulaziz; Alsadoun, Rgad; Haddad, Bandar (Galen Medical Journal, 2019)
Background: Depression, which is characterized by persistent sadness, is a highly prevalent and serious medical disease that affects more than 300 million individuals worldwide. It is hypothesized that the onset of depressive symptoms in medical students occurs due to prolonged exposure to the stressful environment of medical colleges. Hence, we aimed to determine the presence of depressive symptoms and compare the level of depression between the first-year and fifth-year medical students in Riyadh city, Saudi Arabia. Materials and Methods: This cross-sectional study was performed with convenient sampling from 2 medical colleges in Riyadh in the Kingdom of Saudi Arabia from October to November 2017. The English version of Beck’s Depression Inventory questionnaire was used in this study. Statistical analysis was administered using SPSS via chi-square test, and P-value less than 0.05 was considered statistically significant. Results: The questionnaire was answered by 241 participants. The age variable shows a bimodal distribution. The mean age of first-year and fifth-year students was 19±0.8 years and 23±2.1 years, respectively. Fifth-year students comprised 53.5% of the total sample, and male students accounted for 63.1% of the total sample. After analysis, the results show that male students scored higher than female students on the lower side of the scale in both years. Most of the first-year female students scored a higher level of depression compared with male students (P=0.001), whereas no difference between males and females (P=0.04) was found in the fifth-year students’ data. Conclusion: Our study shows a new pattern of reported depressive symptoms among first- and fifth-year medical students. In addition, the study suggests that depression is more common in female medical students as compared with their male counterparts. For future studies, we recommend using randomized sampling in a cohort study including all levels of medical students to further investigate and confirm the findings.[GMJ.2019;8:e1497]